The Relationship between Social Support and Depression in the LGBT+ population: A Meta-analysis - Laura BERCEA; Sebastian PINTEA; Éva KÁLLAY (Studia Universitatis Babes-Bolyai, 2023)
Introduction: Previous research investigating the relationship between social support and depression in the LGBT+ community yielded mixed results. Considering that the LGBT+ population has a high prevalence of mental disorders and is frequently victim of discrimination, it would be essential to know if social support is related to the depressive symptoms its representatives face. The main purpose of this meta-analysis was to clarify whether there is a correlation between social support and depression in the LGBT+ population and to identify moderators of this relationship. Methods: EBSCO, PubMed, and PsychNET databases were searched. Studies that reported statistical indicators for the relationship between social support and depression in an LGBT+ sample were included in this meta-analysis. Results: 48 studies were eligible for the meta-analysis. Our results show that there is a significant negative moderate relationship between social support and depression in the LGBT+ community. The heterogeneity of the results in the literature is partially explained by the way social support was defined and measured, by gender, sexual orientation, and ethnicity. Limitations and implications of the current study are discussed. Discussion: Practical implications of these results include promoting social support, and acceptance at individual and social levels, with more emphasis on policies and practices that foster well-being and a positive climate, that encourage information sharing, and offering support related to LGBT+ issues. It is also important to create safe spaces for sexual minority youth. Considering the LGBT+ adults, all these aspects can be implemented as well in work contexts, to promote safe spaces and accepting attitudes in the workspace.